Effects of entomopathogenic fungus, metarhizium anisopliae as bio control agent of fruit flies, bactrocera occipitalis and bactrocena philippirensis. - De leon, Sarah (Iloilo City UPHSI, 2006)
One of the most important mango pests is the fruit fly. In the Philippines, the two most common species of economic importance are the Bactrocera occipitalis and Bactrocera philippinensis since the species restrict the market expansion of mango industry. Pest management methods that have been suggested to control these fruit flies using synthetic chemicals but other solutions such as biocontrol agents use entomopathogenic fungus like Metarhizium anisopliae. An experiment was conducted to determine the effect of varying concentrations of Metarhizium anisopliae to the Bactrocera occipitalis and Bactrocera philippinensis under laboratory conditions. Results showed mortality among tested conditions (1x10^16, 1x10^7, 1x10^8, and 1x10^9 conidia/ml) was significantly different for both fly species. All the concentrations were effective in controlling both fruit fly species but the most effective were 1x10^8 (92.08+/-13.33%) and 1x10^9 (99.82 +/- 3.33%) conidia/ml for Bactrocera occipitalis was Bactrocera philippinensis respectively. LT50 occured earlier at concentrations 1x10^8 (4.00 days) and 1x10^9 (4.52 days) condia/ml for Bactrocera occipitalis and Bactrocera philippinensis respectively. Based on linear regression, mortality was directly related to concentration for Bactrocera philippinensis only. And, Bactrocera occipitalis was more susceptible to Metarhizium anisoplia than Bactrocera philippinensis.
Research II : Research Manuscripts
Keywords: Entomopathogenic fungus